India versus China: A review of the Aksai Chin border dispute - Nadeem Shafiq (Journal of Political Studies, 2011)
China and India have a border dispute over the Aksai Chin region which is situated between the Chinese selfgoverning regions of Xinjiang and Tibet. It has been claimed by India as part of Ladakh section of the state of Jammu and Kashmir. The high-altitude barren plateau of Aksai Chin is almost unpopulated and has a small number of natural resources. Both countries fought a brief war in 1962 over the disputed land culminating in the Chinese victory. After long stalemate, on 7 September 1993, China and India signed an agreement to decrease stress along with their borders. Meanwhile, on 2 March 1963, Pakistan conceded its northern claim line in Pakistani-controlled Kashmir to China in favor of a more southerly boundary along the Karakoram Range. The extinction of this boundary at the Karakoram Pass on the Chinese line of control suggests that Pakistan recognizes Chinese sovereignty over Aksai Chin.